1998
DOI: 10.1086/306346
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic VLBI Observations of EGRET Blazars

Abstract: ABSTRACT, and we derive lower limits on the ejection times of any such components. The misalignment angle distribution of the EGRET sources is compared to the distribution for blazars as a whole, and we Ðnd that EGRET sources belong preferentially to neither the aligned nor the misaligned population. We also compare the average values for the apparent velocities and Doppler beaming factors for the EGRET and non-EGRET blazars, and Ðnd no signiÐcant di †erences. We thus Ðnd no indication, within the measurement … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…The very weak south-western extension of A could be related to the faint intermediate component in Kellermann et al (1998) and component C in Pyatunina et al (2000). Compared with the 2 GHz data of Piner et al (1998), with a resolution similar to ours, the separation we measure at 8.4 GHz between A and D strengthens its constancy over a time baseline of ten years, giving a proper motion of 0.02 ± 0.03 mas/yr, corresponding to β app ≈ 0.3±0.44. Furthermore, our 15 GHz image shows a separation between A and the bright features D1 and D2 equal to that reported by Kellermann et al (2004) at the same frequency over a six-year interval, confirming that no apparent motion is present.…”
Section: +149supporting
confidence: 81%
See 1 more Smart Citation
“…The very weak south-western extension of A could be related to the faint intermediate component in Kellermann et al (1998) and component C in Pyatunina et al (2000). Compared with the 2 GHz data of Piner et al (1998), with a resolution similar to ours, the separation we measure at 8.4 GHz between A and D strengthens its constancy over a time baseline of ten years, giving a proper motion of 0.02 ± 0.03 mas/yr, corresponding to β app ≈ 0.3±0.44. Furthermore, our 15 GHz image shows a separation between A and the bright features D1 and D2 equal to that reported by Kellermann et al (2004) at the same frequency over a six-year interval, confirming that no apparent motion is present.…”
Section: +149supporting
confidence: 81%
“…Although the authors described the source as a core-jet we thought that it could be an asymmetric double with a weak core and therefore worth observing again. Additional images at 2.3 and 8.5 GHz from geodetic VLBI observations (Piner & Kingham 1998; Pyatunina et al 2000) and from VLBA observations at 15, 22 GHz (Wiik et al 2001) and 43 GHz (Pyatunina et al 2000) are also available. From these images our component A turned out to have a rather complex structure, being resolved into a bright component (called A in Pyatunina et al 2000) plus two weaker ones (B and C in Pyatunina et al 2000), which show activity and possibly superluminal motions.…”
Section: +149mentioning
confidence: 99%
“…Figure 18 shows that the components move along curved path. For comparison, we also included the data from the geodetic VLBI observation by Piner & Kingham (1998) (estimates from their Fig. 10) during period from 1988 to 1996 in Fig.…”
Section: A Helical Patternmentioning
confidence: 99%
“…The parsec-scale core was identified by Kovalev et al (2009) ;Pushkarev et al (2010) as a likely location for both the γ-ray and radio flares, which appears within typical timescales of up to a few months of each other. Many γ-ray flares are connected with the ejection of a newly born components (e.g., Jorstad et al 2001;Agudo et al 2011) but sometimes no observed components can be associated with the γ-ray flares (e.g., Piner & Kingham 1998), though many sources show dual properties (e.g., Marscher et al 2008;Ramakrishnan et al 2014;Morozova et al 2014).…”
Section: Introductionmentioning
confidence: 99%